Controllable microchannel reactor green methanol preparation method based on low-temperature plasma activation
By using a low-temperature plasma-activated controlled microchannel reactor and intelligent control system in the CO2 hydrogenation and methanol production technology, combined with high-efficiency catalysts, the problems of high energy consumption and low selectivity in the existing technology are solved, and the efficient conversion of CO2 and selective synthesis of methanol are achieved, which has significant industrial application potential.
Patent Information
- Application Number
- CN202411858110.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing CO2 hydrogenation methanol production technology has problems such as high energy consumption, low selectivity, unreasonable reactor design, low mass transfer and heat transfer efficiency, and easy catalyst deactivation, which seriously restricts industrial applications.
The controlled microchannel reactor based on low-temperature plasma activation is adopted, combined with intelligent control system and high-efficiency catalyst to achieve efficient CO2 conversion and selective synthesis of methanol. The method includes preparing microchannel reactors, catalysts and microchannel wall coatings, generating low-temperature plasma using a dielectric barrier discharge DBD plasma generator, and adjusting reaction parameters in real time through an intelligent control system.
The CO2 conversion rate was increased to 75.8%, the methanol selectivity reached 97.3%, the energy efficiency increased to 68.9%, the activity retention rate of the catalyst was as high as 97.5% after 500 hours, and efficient conversion was achieved at a relatively low temperature of 180°C, which has important industrial application value.
Smart Images

Figure BDA0005192442170000141 
Figure BDA0005192442170000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of green methanol, and in particular to a method for preparing green methanol in a controllable microchannel reactor based on low-temperature plasma activation. Background Art
[0002] In recent years, as the global climate change problem becomes increasingly serious, CO2 emission reduction and resource utilization have become the focus of scientific research and industry. As an important chemical raw material and clean fuel, the green synthesis method of methanol has attracted much attention. Traditional methanol synthesis is mainly based on fossil fuels, which not only increases carbon emissions, but also faces the challenge of resource depletion. Therefore, the development of green methanol synthesis technology using CO2 as raw material has important practical significance.
[0003] At present, the main technical routes for producing methanol by hydrogenation of CO2 include high temperature and high pressure catalytic method and low temperature plasma method. Although the high temperature and high pressure catalytic method is mature, it has problems such as high energy consumption and low selectivity. Although the low temperature plasma method can activate CO2 under mild conditions, its conversion efficiency and product selectivity still need to be improved. In addition, the existing technology generally has problems such as unreasonable reactor design, low mass and heat transfer efficiency, and easy deactivation of catalysts, which seriously restricts industrial application. Summary of the invention
[0004] In view of the above technical difficulties, the present invention proposes a green methanol production method based on a controllable microchannel reactor activated by low-temperature plasma. The method cleverly combines low-temperature plasma technology, microchannel reactor, intelligent control system and efficient catalyst to achieve efficient conversion of CO2 and selective synthesis of methanol.
[0005] The object of the present invention is to provide a green methanol preparation method in a controllable microchannel reactor based on low-temperature plasma activation, comprising the following steps:
[0006] (1) preparing a microchannel reactor, wherein the microchannel reactor is made of 316L stainless steel, the inner wall of which is treated by plasma enhanced chemical vapor deposition (PECVD) to deposit a 5-10 μm thick titanium nitride coating; the microchannel reactor has a bionic tree-like hierarchical structure, the main channel diameter is 500-1000 μm, the secondary channel diameter is 100-300 μm, and the minimum channel diameter is 20-50 μm; the total length of the reactor is 300-500 mm, the width is 100-200 mm, and the height is 50-100 mm;
[0007] (2) preparing a catalyst, including a main catalyst Cu / ZnO / Al2O3 and a co-catalyst rare earth-doped CeO2;
[0008] (3) preparing a microchannel wall coating, mixing the catalyst prepared in step (2) with a binder to form a slurry, coating it by vacuum suction method, drying it, calcining it at 350° C. for 2 hours, repeating the coating process 3 times, and obtaining a catalyst coating with a thickness of 20-30 μm;
[0009] (4) using a dielectric barrier discharge (DBD) plasma generator to generate low-temperature plasma at a voltage of 10-30 kV and a frequency of 10-50 kHz;
[0010] (5) A mixed gas of CO2, H2 and Ar is introduced into a microchannel reactor and reacted at a temperature of 120-180°C and a pressure of 3-5 MPa, with a GHSV of 5000-10000 h -1 ;
[0011] (6) Using intelligent control systems to adjust reaction parameters in real time;
[0012] (7) The reaction products are subjected to condensation separation, membrane separation and molecular sieve adsorption to obtain a high-purity methanol product.
[0013] Preferably, the preparation method of the main catalyst Cu / ZnO / Al2O3 in step (2) comprises:
[0014] First, 100-150 parts by weight of copper (II) nitrate trihydrate, 50-80 parts by weight of zinc nitrate hexahydrate, and 30-50 parts by weight of aluminum nitrate nonahydrate are dissolved in 500-800 parts by weight of deionized water;
[0015] Next, add 80-120 parts by weight of citric acid monohydrate and continue stirring;
[0016] Then, heat the solution to 80-90°C and evaporate it to a paste;
[0017] Again, dried at 110°C for 12 hours;
[0018] Finally, the powder was ground and calcined at 400°C for 4 hours, cooled, ground again, and passed through a 200-mesh sieve.
[0019] Preferably, 0.1-0.5 parts by weight of palladium (II) chloride is added during the preparation of the main catalyst Cu / ZnO / Al2O3.
[0020] Preferably, the preparation method of the rare earth-doped CeO2 as a promoter in step (2) comprises:
[0021] First, 80-120 parts by weight of cerium (III) nitrate hexahydrate, 5-10 parts by weight of lanthanum (III) nitrate hexahydrate, and 3-8 parts by weight of praseodymium (III) nitrate hexahydrate are dissolved in 400-600 parts by weight of deionized water;
[0022] Next, add 150-200 parts by weight of urea and continue stirring;
[0023] Then, the solution was transferred to a hydrothermal reactor and reacted at 180 °C for 12 h;
[0024] Again, after cooling, centrifugation was performed and the mixture was washed three times with deionized water;
[0025] Finally, the product was vacuum dried at 60°C for 12 hours, ground and calcined at 500°C for 4 hours, cooled and ground again, and passed through a 200-mesh sieve.
[0026] Preferably, the composition of the microchannel wall coating slurry in step (3) is:
[0027] 50-70 parts by weight of main catalyst powder, 10-20 parts by weight of co-catalyst powder, 5-10 parts by weight of polyvinyl alcohol PVA, Mw: 89,000-98,000, 3-8 parts by weight of hydroxypropyl methylcellulose HPMC, 0.5-2 parts by weight of graphene oxide and 100-150 parts by weight of deionized water.
[0028] Preferably, the electrode material of the plasma generator in step (4) is a platinum-coated titanium mesh, and the dielectric layer is α-alumina ceramic with a thickness of 0.5-1.0 mm.
[0029] Preferably, the mixed gas in step (5) comprises: 100 parts by weight of CO2, 300-400 parts by weight of H2, 50-100 parts by weight of Ar and 0.1-1 parts by weight of CH4.
[0030] Preferably, in step (6), the intelligent control system adopts a deep reinforcement learning DRL algorithm, specifically PPO, and the neural network structure is a 4-layer fully connected network with 128 nodes in each layer, and the activation function is ReLU.
[0031] Preferably, the condensation separation in step (7) adopts a spiral plate heat exchanger, the cooling medium is a 30% w / w ethylene glycol aqueous solution, the cooling temperature gradient is 5°C → -5°C → -15°C, and the residence time of each stage is 60-90 seconds.
[0032] Preferably, the step (7) further comprises a distillation step:
[0033] The tower is packed with 316L stainless steel, with a height of 3m and an inner diameter of 0.3m;
[0034] The packing is stainless steel structured packing Sullener Mellapak 250Y;
[0035] The reflux ratio is 1.2-1.5;
[0036] The tower top temperature is 64.5±0.5℃;
[0037] The tower bottom temperature is 78±1℃.
[0038] The core innovations and beneficial effects of the present invention can be summarized as follows:
[0039] The core innovation of the present invention is that: first, the dielectric barrier discharge (DBD) plasma technology is used to achieve efficient activation of CO2 and H2 under relatively mild conditions. The high-energy electrons, excited molecules and free radicals generated in the plasma significantly reduce the activation energy barrier of the reaction. Secondly, a microchannel reactor with a bionic tree-like hierarchical structure is designed to greatly improve the mass transfer and heat transfer efficiency. The high specific surface area of the microchannel not only enhances the gas-solid contact, but also facilitates the uniform distribution of the plasma, thereby improving the reaction efficiency and selectivity.
[0040] Furthermore, the present invention has developed a new type of Cu / ZnO / Al2O3 catalyst, which significantly improves the low-temperature activity and stability of the catalyst by adding trace amounts of Pd and rare earth element-doped CeO2. The synergistic effect of Cu and Pd enhances the adsorption and activation of CO2, while the oxygen vacancies of CeO2 promote the conversion of intermediates. This multi-component catalyst forms a unique synergistic effect with plasma, further reducing the reaction energy barrier.
[0041] In addition, the present invention also introduces an intelligent control system based on deep reinforcement learning to achieve real-time optimization and adjustment of reaction parameters. This not only improves the stability and controllability of the reaction, but also can adaptively adjust the process parameters according to changes in raw material composition and reaction conditions, greatly enhancing the flexibility of industrial applications.
[0042] Finally, the present invention further improves the conversion efficiency of CO2 by optimizing the reaction gas composition, especially adding a trace amount of CH4 as a promoter. CH4 is more easily activated in plasma, and the generated active intermediates can promote the dissociation of CO2, thereby accelerating the entire reaction process.
[0043] The organic combination of these innovative points has produced a significant synergistic effect, which has enabled the present invention to achieve breakthroughs in multiple key indicators: CO2 conversion rate increased to 75.8%, methanol selectivity reached 97.3%, energy efficiency increased to 68.9%, and the catalyst activity retention rate after 500 hours was as high as 97.5%. It is particularly worth mentioning that the present invention can achieve such efficient conversion at a relatively low temperature of 180°C, which is of great significance for industrial applications.
[0044] In summary, the present invention not only solves the problems of low CO2 conversion efficiency, high energy consumption, poor selectivity, etc. in the prior art, but also achieves a technological leap in green methanol synthesis through a multidisciplinary cross-integration method. This new preparation method provides a new efficient, economical and environmentally friendly way for CO2 resource utilization, and is expected to play an important role in alleviating the greenhouse effect and promoting the development of the circular economy. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] This embodiment provides a green methanol production method using a controllable microchannel reactor based on low-temperature plasma activation. The method makes full use of the selective activation effect of low-temperature plasma and combines the efficient mass transfer and heat transfer characteristics of the microchannel reactor to achieve efficient conversion of CO2 and green synthesis of methanol.
[0048] Specifically, the method comprises the following steps:
[0049] (1) First, a microchannel reactor was prepared. 316L stainless steel was used as the substrate, and a 5 μm thick titanium nitride (TiN) coating was deposited on the inner wall by plasma enhanced chemical vapor deposition (PECVD). The reactor was designed with a bionic tree-like hierarchical structure, in which the main channel diameter was 500 μm, the secondary channel diameter was 100 μm, and the minimum channel diameter was 20 μm. The total length of the reactor was 300 mm, the width was 100 mm, and the height was 50 mm. This design not only provided a uniform flow field distribution, but also significantly improved the mass transfer and heat transfer efficiency.
[0050] (2) Secondly, prepare the catalyst. The preparation method of the main catalyst Cu / ZnO / Al2O3 is as follows: 100 parts by weight of copper (II) nitrate trihydrate, 50 parts by weight of zinc nitrate hexahydrate, and 30 parts by weight of aluminum nitrate nonahydrate are dissolved in 500 parts by weight of deionized water. Then 80 parts by weight of citric acid monohydrate are added and stirring is continued for 60 minutes. The solution is heated to 80°C and evaporated to a paste. After drying at 110°C for 12 hours, it is ground and calcined at 400°C for 4 hours. After cooling, it is ground again and passed through a 200-mesh sieve.
[0051] The preparation method of the co-catalyst rare earth doped CeO2 is as follows: 80 parts by weight of cerium (III) nitrate hexahydrate, 5 parts by weight of lanthanum (III) nitrate hexahydrate, and 3 parts by weight of praseodymium (III) nitrate hexahydrate are dissolved in 400 parts by weight of deionized water. 150 parts by weight of urea are added and stirring is continued for 60 minutes. The solution is transferred to a hydrothermal reactor and reacted at 180°C for 12 hours. After cooling, centrifugation is performed and the mixture is washed 3 times with deionized water. Vacuum drying is performed at 60°C for 12 hours, and after grinding, it is roasted at 500°C for 4 hours. After cooling, it is ground again and passed through a 200 mesh sieve.
[0052] (3) Then, prepare the microchannel wall coating. Mix 50 parts by weight of main catalyst powder, 10 parts by weight of co-catalyst powder, 5 parts by weight of polyvinyl alcohol (PVA, Mw: 89,000-98,000), 3 parts by weight of hydroxypropyl methylcellulose (HPMC), 0.5 parts by weight of graphene oxide (GO) and 100 parts by weight of deionized water to form a slurry. Coating is performed by vacuum suction method, dried at 60°C for 2 hours, and then calcined at 350°C for 2 hours. Repeat the coating process 3 times to finally obtain a catalyst coating with a thickness of 20 μm.
[0053] (4) Next, a plasma generating device was set up. A dielectric barrier discharge (DBD) plasma generator was used, with a voltage of 10 kV and a frequency of 10 kHz. The electrode material was a platinum-coated titanium mesh, and the dielectric layer was α-alumina ceramic with a thickness of 0.5 mm.
[0054] (5) Then, the reaction process was controlled. 100 parts by weight of CO2, 300 parts by weight of H2, 50 parts by weight of Ar and 0.1 parts by weight of CH4 were mixed and introduced into the microchannel reactor. The reaction temperature was 120°C, the pressure was 3 MPa, and the space velocity (GHSV) was 5000 h -1 The plasma discharge power was set to 20 W, the discharge frequency to 20 kHz, and the duty cycle to 30%.
[0055] (6) At the same time, an intelligent control system is used to adjust the reaction parameters in real time. The system is based on the deep reinforcement learning (DRL) algorithm, specifically using Proximal Policy Optimization (PPO). The neural network structure is a 4-layer fully connected network with 128 nodes in each layer and the activation function is ReLU.
[0056] (7) Finally, the reaction products were separated and purified. First, condensation separation was performed using a spiral plate heat exchanger, the cooling medium was a 30% w / w ethylene glycol aqueous solution, the cooling temperature gradient was 5°C → -5°C → -15°C, and the residence time for each stage was 60 seconds. Then membrane separation was performed using a polyether block amide (PEBA) composite membrane. MH1657, operating temperature is 40℃, pressure is 0.2MPa. Finally, molecular sieve adsorption is carried out, 5A molecular sieve is used, regeneration temperature is 280℃, and regeneration time is 3 hours.
[0057] Preferably, in the embodiment of the present invention, a distillation step is further included: a 316L stainless steel packed tower is used, with a height of 3m and an inner diameter of 0.3m. The packing is a stainless steel structured packing Sulzer Mellapak 250Y. The reflux ratio is 1.2, the tower top temperature is 64.5°C, and the tower bottom temperature is 78°C.
[0058] Example 2
[0059] This example provides another green methanol production method based on low-temperature plasma activation in a controllable microchannel reactor. The method is based on Example 1 and some parameters are adjusted to explore the reaction effects under different conditions.
[0060] Specifically, the method comprises the following steps:
[0061] (1) First, a microchannel reactor was prepared. The same 316L stainless steel substrate as in Example 1 was used, but the thickness of the titanium nitride (TiN) coating was increased to 10 μm. The main channel diameter of the reactor was adjusted to 750 μm, the secondary channel diameter was 200 μm, and the minimum channel diameter was 35 μm. The total length of the reactor was increased to 400 mm, the width was 150 mm, and the height was 75 mm.
[0062] (2) Secondly, prepare the catalyst. The preparation method of the main catalyst Cu / ZnO / Al2O3 is as follows: dissolve 125 parts by weight of copper (II) nitrate trihydrate, 65 parts by weight of zinc nitrate hexahydrate, and 40 parts by weight of aluminum nitrate nonahydrate in 650 parts by weight of deionized water. Add 100 parts by weight of citric acid monohydrate and continue stirring for 60 minutes. Heat the solution to 85°C and evaporate to a paste. After drying at 110°C for 12 hours, grind and calcine at 400°C for 4 hours. After cooling, grind again and pass through a 200-mesh sieve.
[0063] The preparation method of the co-catalyst rare earth doped CeO2 is as follows: 100 parts by weight of cerium (III) nitrate hexahydrate, 7.5 parts by weight of lanthanum (III) nitrate hexahydrate, and 5.5 parts by weight of praseodymium (III) nitrate hexahydrate are dissolved in 500 parts by weight of deionized water. 175 parts by weight of urea are added and stirring is continued for 60 minutes. The solution is transferred to a hydrothermal reactor and reacted at 180°C for 12 hours. After cooling, centrifugation is performed and the mixture is washed 3 times with deionized water. Vacuum drying is performed at 60°C for 12 hours, and after grinding, it is roasted at 500°C for 4 hours. After cooling, it is ground again and passed through a 200 mesh sieve.
[0064] (3) Then, prepare the microchannel wall coating. 60 parts by weight of main catalyst powder, 15 parts by weight of co-catalyst powder, 7.5 parts by weight of polyvinyl alcohol (PVA, Mw: 93,500), 5.5 parts by weight of hydroxypropyl methylcellulose (HPMC), 1.25 parts by weight of graphene oxide (GO) and 125 parts by weight of deionized water are mixed to form a slurry. The coating is carried out by vacuum suction method, dried at 60°C for 2 hours, and then calcined at 350°C for 2 hours. Repeat the coating process 3 times to finally obtain a catalyst coating with a thickness of 25 μm.
[0065] (4) Next, a plasma generating device was set up. A dielectric barrier discharge (DBD) plasma generator was used, with a voltage of 20 kV and a frequency of 30 kHz. The electrode material was a platinum-coated titanium mesh, and the dielectric layer was α-alumina ceramic with a thickness of 0.75 mm.
[0066] (5) Then, the reaction process was controlled. 100 parts by weight of CO2, 350 parts by weight of H2, 75 parts by weight of Ar and 0.55 parts by weight of CH4 were mixed and introduced into the microchannel reactor. The reaction temperature was 150°C, the pressure was 4 MPa, and the space velocity (GHSV) was 7500 h -1 The plasma discharge power was set to 35 W, the discharge frequency to 30 kHz, and the duty cycle to 40%.
[0067] (6) At the same time, an intelligent control system is used to adjust the reaction parameters in real time. The system settings are the same as those in Example 1.
[0068] (7) Finally, the reaction product was separated and purified. The condensation separation used a spiral plate heat exchanger, the cooling medium was a 30% w / w ethylene glycol aqueous solution, the cooling temperature gradient was 5°C → -5°C → -15°C, and the residence time per stage was 75 seconds. The membrane separation and molecular sieve adsorption steps were the same as in Example 1.
[0069] Preferably, in this embodiment, the reflux ratio of the distillation step is adjusted to 1.35, the tower top temperature is 64.75°C, and the tower bottom temperature is 77.5°C.
[0070] Example 3
[0071] This embodiment provides a third method for preparing green methanol in a controllable microchannel reactor based on low-temperature plasma activation, which further optimizes the reaction conditions and catalyst composition to improve CO2 conversion and methanol selectivity.
[0072] Specifically, the method comprises the following steps:
[0073] (1) First, a microchannel reactor was prepared. A 316L stainless steel substrate was used, and a 7.5 μm thick titanium nitride (TiN) coating was deposited on the inner wall by PECVD. The main channel diameter of the reactor was 1000 μm, the secondary channel diameter was 300 μm, and the minimum channel diameter was 50 μm. The total length of the reactor was 500 mm, the width was 200 mm, and the height was 100 mm.
[0074] (2) Secondly, prepare the catalyst. The preparation method of the main catalyst Cu / ZnO / Al2O3 is as follows: dissolve 150 parts by weight of copper nitrate (II) trihydrate, 80 parts by weight of zinc nitrate hexahydrate, and 50 parts by weight of aluminum nitrate nonahydrate in 800 parts by weight of deionized water. Add 120 parts by weight of citric acid monohydrate and 0.5 parts by weight of palladium (II) chloride, and continue stirring for 60 minutes. Heat the solution to 90°C and evaporate to a paste. After drying at 110°C for 12 hours, grind and calcine at 400°C for 4 hours. Grind again after cooling and pass through a 200-mesh sieve.
[0075] The preparation method of the co-catalyst rare earth doped CeO2 is as follows: 120 parts by weight of cerium (III) nitrate hexahydrate, 10 parts by weight of lanthanum (III) nitrate hexahydrate, and 8 parts by weight of praseodymium (III) nitrate hexahydrate are dissolved in 600 parts by weight of deionized water. 200 parts by weight of urea are added and stirring is continued for 60 minutes. The solution is transferred to a hydrothermal reactor and reacted at 180°C for 12 hours. After cooling, centrifugation is performed and the mixture is washed 3 times with deionized water. Vacuum drying is performed at 60°C for 12 hours, and after grinding, it is roasted at 500°C for 4 hours. After cooling, it is ground again and passed through a 200 mesh sieve.
[0076] (3) Then, prepare the microchannel wall coating. 70 parts by weight of main catalyst powder, 20 parts by weight of co-catalyst powder, 10 parts by weight of polyvinyl alcohol (PVA, Mw: 98,000), 8 parts by weight of hydroxypropyl methylcellulose (HPMC), 2 parts by weight of graphene oxide (GO) and 150 parts by weight of deionized water are mixed to form a slurry. The coating is carried out by vacuum suction method, dried at 60°C for 2 hours, and then calcined at 350°C for 2 hours. Repeat the coating process 3 times to finally obtain a 30μm thick catalyst coating.
[0077] (4) Next, a plasma generating device was set up. A dielectric barrier discharge (DBD) plasma generator was used, with a voltage of 30 kV and a frequency of 50 kHz. The electrode material was a platinum-coated titanium mesh, and the dielectric layer was α-alumina ceramic with a thickness of 1.0 mm.
[0078] (5) Then, the reaction process was controlled. 100 parts by weight of CO2, 400 parts by weight of H2, 100 parts by weight of Ar and 1 part by weight of CH4 were mixed and introduced into the microchannel reactor. The reaction temperature was 180°C, the pressure was 5 MPa, and the space velocity (GHSV) was 10000 h -1 The plasma discharge power was set to 50 W, the discharge frequency to 40 kHz, and the duty cycle to 50%.
[0079] (6) At the same time, an intelligent control system is used to adjust the reaction parameters in real time. The system settings are the same as those in Example 1.
[0080] (7) Finally, the reaction product was separated and purified. The condensation separation used a spiral plate heat exchanger, the cooling medium was a 30% w / w ethylene glycol aqueous solution, the cooling temperature gradient was 5°C → -5°C → -15°C, and the residence time per stage was 90 seconds. The membrane separation and molecular sieve adsorption steps were the same as in Example 1.
[0081] Preferably, in this embodiment, the reflux ratio of the distillation step is adjusted to 1.5, the tower top temperature is 65°C, and the tower bottom temperature is 79°C.
[0082] Example 4
[0083] This embodiment provides a fourth method for preparing green methanol in a controllable microchannel reactor based on low-temperature plasma activation. The method aims to explore the reaction effect in an intermediate parameter range and further optimize the catalyst composition and reaction conditions.
[0084] Specifically, the method comprises the following steps:
[0085] (1) First, a microchannel reactor was prepared. A 316L stainless steel substrate was used, and an 8 μm thick titanium nitride (TiN) coating was deposited on the inner wall by PECVD. The main channel diameter of the reactor was 800 μm, the secondary channel diameter was 250 μm, and the minimum channel diameter was 40 μm. The total length of the reactor was 450 mm, the width was 175 mm, and the height was 85 mm.
[0086] (2) Secondly, prepare the catalyst. The preparation method of the main catalyst Cu / ZnO / Al2O3 is as follows: dissolve 135 parts by weight of copper nitrate (II) trihydrate, 70 parts by weight of zinc nitrate hexahydrate, and 45 parts by weight of aluminum nitrate nonahydrate in 700 parts by weight of deionized water. Add 110 parts by weight of citric acid monohydrate and 0.3 parts by weight of palladium (II) chloride, and continue stirring for 60 minutes. Heat the solution to 87°C and evaporate to a paste. After drying at 110°C for 12 hours, grind and calcine at 400°C for 4 hours. Grind again after cooling and pass through a 200-mesh sieve.
[0087] The preparation method of the co-catalyst rare earth doped CeO2 is as follows: 110 parts by weight of cerium (III) nitrate hexahydrate, 8 parts by weight of lanthanum (III) nitrate hexahydrate, and 6 parts by weight of praseodymium (III) nitrate hexahydrate are dissolved in 550 parts by weight of deionized water. 185 parts by weight of urea are added and stirring is continued for 60 minutes. The solution is transferred to a hydrothermal reactor and reacted at 180°C for 12 hours. After cooling, centrifugation is performed and the mixture is washed 3 times with deionized water. Vacuum drying is performed at 60°C for 12 hours, and after grinding, it is roasted at 500°C for 4 hours. After cooling, it is ground again and passed through a 200 mesh sieve.
[0088] (3) Then, prepare the microchannel wall coating. 65 parts by weight of main catalyst powder, 18 parts by weight of co-catalyst powder, 8.5 parts by weight of polyvinyl alcohol (PVA, Mw: 95,000), 7 parts by weight of hydroxypropyl methylcellulose (HPMC), 1.5 parts by weight of graphene oxide (GO) and 135 parts by weight of deionized water are mixed to form a slurry. The coating is carried out by vacuum suction method, dried at 60°C for 2 hours, and then calcined at 350°C for 2 hours. Repeat the coating process 3 times to finally obtain a catalyst coating with a thickness of 27 μm.
[0089] (4) Next, a plasma generating device was set up. A dielectric barrier discharge (DBD) plasma generator was used, with a voltage of 25 kV and a frequency of 40 kHz. The electrode material was a platinum-coated titanium mesh, and the dielectric layer was α-alumina ceramic with a thickness of 0.85 mm.
[0090] (5) Then, the reaction process was controlled. 100 parts by weight of CO2, 375 parts by weight of H2, 85 parts by weight of Ar and 0.8 parts by weight of CH4 were mixed and introduced into the microchannel reactor. The reaction temperature was 165°C, the pressure was 4.5 MPa, and the space velocity (GHSV) was 8500 h -1 The plasma discharge power was set to 42 W, the discharge frequency to 35 kHz, and the duty cycle to 45%.
[0091] (6) At the same time, an intelligent control system is used to adjust the reaction parameters in real time. The system settings are the same as those in Example 1.
[0092] (7) Finally, the reaction product was separated and purified. The condensation separation used a spiral plate heat exchanger, the cooling medium was a 30% w / w ethylene glycol aqueous solution, the cooling temperature gradient was 5°C → -5°C → -15°C, and the residence time per stage was 80 seconds. The membrane separation and molecular sieve adsorption steps were the same as in Example 1.
[0093] Preferably, in this embodiment, the reflux ratio of the distillation step is adjusted to 1.4, the tower top temperature is 64.8°C, and the tower bottom temperature is 78.5°C.
[0094] These examples fully demonstrate the feasibility and flexibility of the method of the present invention, and also reflect the important role of innovations such as low-temperature plasma activation, microchannel reactor design, catalyst optimization, and intelligent control system in practical applications. This green methanol preparation method can not only achieve efficient conversion of CO2 under mild conditions, but also has the advantages of low energy consumption and high selectivity, providing a new technical path for solving energy and environmental problems.
[0095] Comparative Example 1: No plasma activation
[0096] This comparative example is intended to verify the importance of low-temperature plasma activation. The method is basically the same as Example 1, but no plasma generator is used. The specific steps are as follows:
[0097] First, a microchannel reactor and a catalyst were prepared according to the method of Example 1. Second, the same formula and process were used to prepare the microchannel wall coating. Then, during the reaction, the plasma generator was not enabled, and the reaction was carried out only by thermal catalysis. The reaction temperature, pressure and space velocity were the same as those in Example 1. Finally, the same separation and purification steps were used.
[0098] By comparing the CO2 conversion rate and methanol selectivity of Example 1 and this comparative example, it can be clearly seen that low-temperature plasma activation promotes the reaction. This activation not only reduces the reaction activation energy, but also achieves efficient conversion at a lower temperature, reflecting the innovation and superiority of the present invention.
[0099] Comparative Example 2: Conventional Reactor
[0100] This comparative example is intended to verify the advantages of the microchannel reactor design. The method is as follows:
[0101] First, a conventional fixed bed reactor was used to replace the microchannel reactor, and the reactor volume was equivalent to that of Example 2. Second, the catalyst preparation method was the same as that of Example 2, but the catalyst was loaded onto the γ-Al2O3 particles by an impregnation method. Then, the same plasma generator as that of Example 2 was used. The reaction conditions and separation and purification steps were all the same as those of Example 2.
[0102] By comparing the reaction effects of Example 2 and this comparative example, it can be found that the microchannel reactor has advantages in mass transfer and heat transfer. The microchannel structure not only provides a larger specific surface area, but also achieves a more uniform plasma distribution, thereby improving the reaction efficiency and selectivity.
[0103] Comparative Example 3: No intelligent control system
[0104] This comparative example is intended to verify the effect of the intelligent control system. The method is basically the same as Example 3, but the intelligent control system is not used. The specific steps are as follows:
[0105] The microchannel reactor, catalyst and microchannel wall coating were prepared according to the method of Example 3. During the reaction, fixed parameters were used for operation without real-time adjustment. Other reaction conditions and separation and purification steps were the same as those of Example 3.
[0106] By comparing the reaction stability and product quality of Example 3 and this comparative example, it can be seen that the intelligent control system plays an important role in optimizing reaction parameters and improving product consistency. This real-time adjustment capability is a major advantage of the present invention in industrial applications.
[0107] Comparative Example 4: No graphene oxide added
[0108] This comparative example is intended to verify the role of graphene oxide (GO) in microchannel wall coating. The method is basically the same as Example 4, but GO is not added when preparing the microchannel wall coating. The specific steps are as follows:
[0109] First, a microchannel reactor and a catalyst were prepared according to the method of Example 4. Second, when preparing the microchannel wall coating, 1.5 parts by weight of GO was removed and the amount of the main catalyst powder was increased accordingly. The other steps and parameters were the same as those of Example 4.
[0110] By comparing the catalyst coating stability and reaction effect of Example 4 and this comparative example, it can be found that GO plays an important role in improving the thermal conductivity and mechanical strength of the coating. This improvement not only enhances the service life of the catalyst, but also improves the overall efficiency of the reaction.
[0111] Comparative Example 5: No Palladium Added
[0112] This comparative example is intended to verify the effect of trace palladium addition on the performance of the main catalyst. The method is basically the same as Example 3, but palladium (II) chloride is not added when preparing the main catalyst. The specific steps are as follows:
[0113] A microchannel reactor was prepared according to the method of Example 3. When preparing the main catalyst, 0.5 parts by weight of palladium (II) chloride was removed, and the other steps and parameters remained unchanged. The preparation of the microchannel wall coating, the setting of the plasma generator, the control of the reaction conditions, and the separation and purification of the product were the same as in Example 3.
[0114] By comparing the catalyst activity and selectivity of Example 3 and this comparative example, it can be clearly seen that the addition of trace amounts of palladium plays an important role in improving the low-temperature catalytic activity. This synergistic effect is an innovative point of the present invention in terms of catalyst design.
[0115] Comparative Example 6: No methane added
[0116] This comparative example is intended to verify the role of trace methane as a reaction promoter. The method is basically the same as Example 2, but no methane is added to the reaction gas. The specific steps are as follows:
[0117] First, a microchannel reactor, a catalyst and a microchannel wall coating were prepared according to the method of Example 2. Second, during the reaction, only a mixed gas of CO2, H2 and Ar was used without adding CH4. Other reaction conditions and separation and purification steps were consistent with those of Example 2.
[0118] By comparing the CO2 conversion rate and reaction stability of Example 2 and this comparative example, it can be found that trace methane plays an important role in promoting CO2 activation and improving reaction efficiency. This innovative gas composition design is another highlight of the present invention.
[0119] The results show that the present invention has significant innovation and technical advantages in low-temperature plasma activation, microchannel reactor design, intelligent control system application, catalyst optimization, etc., and provides a new technical path for efficient CO2 conversion and green methanol production.
[0120] In order to comprehensively evaluate the effectiveness and superiority of the method of the present invention, a series of test experiments were designed.
[0121] First, the CO2 conversion rate and methanol selectivity were tested. An online gas chromatograph (Agilent7890B) was used to analyze the reactor outlet gas in real time. The chromatographic column used was an HP-PLOT Q capillary column, the carrier gas was helium, and the flow rate was 30mL / min. The detector used was a thermal conductivity detector (TCD) and a flame ionization detector (FID) in series. Each group of experiments lasted for 24 hours, and samples were taken every 2 hours, and the average value was taken as the final result.
[0122] Secondly, the energy efficiency was evaluated. The input power of the plasma generator was measured using a Yokogawa WT3000E high-precision power analyzer, while the feed flow rate was precisely controlled by a mass flow meter (Bronkhorst EL-FLOW). The energy efficiency is defined as the ratio of the theoretical energy consumption to the actual total energy consumption for producing methanol.
[0123] Then, the stability of the catalyst was tested over a long period of time. The catalyst was operated continuously for 500 hours under the optimal reaction conditions, and the CO2 conversion rate and methanol selectivity were tested every 24 hours to observe their changing trends.
[0124] Again, the mass and heat transfer performance of the microchannel reactor was evaluated. K-type thermocouples (Omega) were installed at different locations in the reactor to measure the uniformity of temperature distribution. At the same time, a pressure sensor (Rosemount3051) was used to measure the pressure drop at the inlet and outlet of the reactor to evaluate the fluid dynamics performance.
[0125] Finally, the purity of the product was analyzed. A gas chromatography-mass spectrometer (Agilent 7890B-5977A) was used to conduct qualitative and quantitative analysis of the final product to detect the purity of methanol and possible trace impurities.
[0126] Based on the above test method, a comprehensive evaluation was conducted on Examples 1-4 and Comparative Examples 1-6. The test results are shown in the following table:
[0127] Table 1: Key performance indicators of various embodiments and comparative examples
[0128]
[0129]
[0130] According to the test results, Example 3 performs best and can be regarded as the best embodiment of the present invention. It reaches the best level in CO2 conversion rate, methanol selectivity, energy efficiency and catalyst stability.
[0131] After in-depth analysis of the test data, it is found that the present invention has the following unexpected technical effects:
[0132] 1. Ultra-high low-temperature activity: Example 3 achieved a CO2 conversion rate of 75.8% at a relatively low temperature of 180°C, which far exceeds the performance of traditional methods at similar temperatures. This significant improvement is due to the synergistic effect of low-temperature plasma and catalysts. The active species generated by plasma greatly reduce the energy barrier for CO2 activation.
[0133] 2. Excellent methanol selectivity: The methanol selectivity of all examples exceeded 95%, especially 97.3% in Example 3. This high selectivity is attributed to the precise reaction control and uniform plasma distribution provided by the microchannel reactor, which effectively inhibits the occurrence of side reactions.
[0134] 3. Significant improvement in energy efficiency: The energy efficiency of Example 3 reaches 68.9%, nearly double that of the traditional method (Comparative Example 1). This is mainly due to the selective activation of low-temperature plasma and the efficient mass and heat transfer of the microchannel reactor, which greatly reduces energy loss.
[0135] 4. Excellent long-term stability: After 500 hours of continuous operation, the activity of Example 3 still remained at 97.5%, which is much higher than that of conventional methods. This stability comes from the optimized catalyst formula and the mild reaction environment of the microchannel reactor, which effectively inhibits the sintering and deactivation of the catalyst.
[0136] 5. Extremely high temperature uniformity: The temperature uniformity of Example 3 reaches ±1.5°C, which is extremely rare in industrial reactors. Such precise temperature control is due to the excellent heat transfer performance of the microchannel structure and the real-time adjustment of the intelligent control system.
[0137] 6. Nearly perfect product purity: The purity of methanol produced in Example 3 is as high as 99.97%, and almost no further purification is required. This high purity is due to the high selectivity of the reaction process and the carefully designed separation and purification process.
[0138] In summary, the present invention has achieved significant breakthroughs in multiple key indicators such as CO2 conversion rate, methanol selectivity, energy efficiency, catalyst stability, etc. through the synergistic effect of innovative points such as low-temperature plasma activation, microchannel reactor design, intelligent control system and optimized catalyst. This green methanol preparation method not only greatly improves the reaction efficiency, but also maximizes energy utilization and minimizes environmental impact, providing a promising new technical path for solving global energy and environmental problems.
[0139] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A green methanol production method based on a controllable microchannel reactor activated by low-temperature plasma, characterized in that: The following steps are involved: (1) preparing a microchannel reactor, wherein the microchannel reactor is made of 316L stainless steel, the inner wall of which is treated by plasma enhanced chemical vapor deposition (PECVD) to deposit a 5-10 μm thick titanium nitride coating; the microchannel reactor has a bionic tree-like hierarchical structure, the main channel diameter is 500-1000 μm, the secondary channel diameter is 100-300 μm, and the minimum channel diameter is 20-50 μm; the total length of the reactor is 300-500 mm, the width is 100-200 mm, and the height is 50-100 mm; (2) preparing a catalyst, including a main catalyst Cu / ZnO / Al2O3 and a co-catalyst rare earth-doped CeO2; (3) preparing a microchannel wall coating, mixing the catalyst prepared in step (2) with a binder to form a slurry, coating it by vacuum suction method, drying it, calcining it at 350° C. for 2 hours, repeating the coating process 3 times, and obtaining a catalyst coating with a thickness of 20-30 μm; (4) using a dielectric barrier discharge (DBD) plasma generator to generate low-temperature plasma at a voltage of 10-30 kV and a frequency of 10-50 kHz; (5) A mixed gas of CO2, H2 and Ar is introduced into a microchannel reactor and reacted at a temperature of 120-180°C and a pressure of 3-5 MPa, with a GHSV of 5000-10000 h -1 ; (6) Using intelligent control systems to adjust reaction parameters in real time; (7) The reaction products are subjected to condensation separation, membrane separation and molecular sieve adsorption to obtain a high-purity methanol product.
2. The method according to claim 1, characterized in that The preparation method of the main catalyst Cu / ZnO / Al2O3 in step (2) comprises: First, 100-150 parts by weight of copper (II) nitrate trihydrate, 50-80 parts by weight of zinc nitrate hexahydrate, and 30-50 parts by weight of aluminum nitrate nonahydrate are dissolved in 500-800 parts by weight of deionized water; Next, add 80-120 parts by weight of citric acid monohydrate and continue stirring; Then, heat the solution to 80-90°C and evaporate it to a paste; Again, dried at 110°C for 12 hours; Finally, the powder was ground and calcined at 400°C for 4 hours, cooled, ground again, and passed through a 200-mesh sieve.
3. The method according to claim 2, characterized in that During the preparation of the main catalyst Cu / ZnO / Al2O3, 0.1-0.5 parts by weight of palladium (II) chloride is also added.
4. The method according to claim 1, characterized in that: The preparation method of the rare earth-doped CeO2 as a promoter in step (2) comprises: First, 80-120 parts by weight of cerium (III) nitrate hexahydrate, 5-10 parts by weight of lanthanum (III) nitrate hexahydrate, and 3-8 parts by weight of praseodymium (III) nitrate hexahydrate are dissolved in 400-600 parts by weight of deionized water; Next, add 150-200 parts by weight of urea and continue stirring; Then, the solution was transferred to a hydrothermal reactor and reacted at 180 °C for 12 h; Again, centrifuge after cooling and wash with deionized water three times; Finally, the product was vacuum dried at 60°C for 12 hours, ground and calcined at 500°C for 4 hours, cooled and ground again, and passed through a 200-mesh sieve.
5. The method according to claim 1, characterized in that The composition of the microchannel wall coating slurry in step (3) is: 50-70 parts by weight of main catalyst powder, 10-20 parts by weight of co-catalyst powder, 5-10 parts by weight of polyvinyl alcohol PVA, Mw: 89,000-98,000, 3-8 parts by weight of hydroxypropyl methylcellulose HPMC, 0.5-2 parts by weight of graphene oxide and 100-150 parts by weight of deionized water.
6. The method according to claim 1, characterized in that In the step (4), the electrode material of the plasma generator is a platinum-coated titanium mesh, and the dielectric layer is α-alumina ceramic with a thickness of 0.5-1.0 mm.
7. The method according to claim 1, characterized in that The composition of the mixed gas in step (5) is: 100 parts by weight of CO2, 300-400 parts by weight of H2, 50-100 parts by weight of Ar and 0.1-1 parts by weight of CH4.
8. The method according to claim 1, characterized in that In the step (6), the intelligent control system adopts a deep reinforcement learning (DRL) algorithm, specifically using PPO, the neural network structure is a 4-layer fully connected network, each layer has 128 nodes, and the activation function is ReLU.
9. The method according to claim 1, characterized in that: In the step (7), the condensation separation adopts a spiral plate heat exchanger, the cooling medium is a 30% w / w ethylene glycol aqueous solution, the cooling temperature gradient is 5°C → -5°C → -15°C, and the residence time of each stage is 60-90 seconds.
10. The method according to claim 1, characterized in that The step (7) further comprises a distillation step: The tower is packed with 316L stainless steel, with a height of 3m and an inner diameter of 0.3m; The packing is stainless steel structured packing Sullener Mellapak 250Y; The reflux ratio is 1.2-1.5; The tower top temperature is 64.5±0.5℃; The tower bottom temperature is 78±1℃.